Palaeocarpological and palaeoclimatic studies of the murtic interglacial flora of the Belarusian upland - Litviniuk, Heorhi I. (Journal of the Belarusian State University. Geography and Geology, 2020)
The Muravian interglacial horizon is the last warm period of time span closest to our time, as well as one of the marking horizons in the complex composed layer of Quaternary deposits in Belarus. The study of the Muravian deposits, as well as an elucidation of the paleogeographic conditions that existed at that time, can make it possible to predict climate changes on our planet in the future. Based on the analysis of palaeocarpological materials obtained by the author in the study of reference sections located within the territory of the Belarusian upland and reflecting the optimal phases of the Muravian interglacial, a brief analysis of the composition of fossil floras is carried out, the conditions for their formation are established, and paleoclimatic reconstructions were performed on the basis of the obtained materials. The data obtained indicate that the average July temperatures at the optimum of the Muravian interglacial on the territory of the Belarusian upland were +17.0 till +24.0 °С for the eastern regions and +17.0 till +21.2 °С for the Grodno upland. The average January temperature ranged from +2.0...+7.0 to –3.0...–7.2 ºC. The results obtained are in good agreement with the data of other methods, in particular, palynological analysis based on the study of fossil pollen and spores. In accordance with the modern climatic indicators of the territory of Belarus, the climate at the optimum of the Muravian interglacial was at least several degrees warmer than the current one, and the winters were much milder.
Keywords: paleogeography; paleoclimat; fossil flora; sozh time; murawinski interglacial period